A bacteriophage-encoded J-domain protein interacts with the DnaK/Hsp70 chaperone and stabilizes the heat-shock factor σ32 of Escherichia coli. - Elsa Perrody; Anne-Marie Cirinesi; Carine Desplats; France Keppel; Françoise Schwager; Samuel Tranier; Costa Georgopoulos; Pierre Genevaux (PLoS Genetics, 2012)
The universally conserved J-domain proteins (JDPs) are obligate cochaperone partners of the Hsp70 (DnaK) chaperone. They stimulate Hsp70's ATPase activity, facilitate substrate delivery, and confer specific cellular localization to Hsp70. In this work, we have identified and characterized the first functional JDP protein encoded by a bacteriophage. Specifically, we show that the ORFan gene 057w of the T4-related enterobacteriophage RB43 encodes a bona fide JDP protein, named Rki, which specifically interacts with the Escherichia coli host multifunctional DnaK chaperone. However, in sharp contrast with the three known host JDP cochaperones of DnaK encoded by E. coli, Rki does not act as a generic cochaperone in vivo or in vitro. Expression of Rki alone is highly toxic for wild-type E. coli, but toxicity is abolished in the absence of endogenous DnaK or when the conserved J-domain of Rki is mutated. Further in vivo analyses revealed that Rki is expressed early after infection by RB43 and that deletion of the rki gene significantly impairs RB43 proliferation. Furthermore, we show that mutations in the host dnaK gene efficiently suppress the growth phenotype of the RB43 rki deletion mutant, thus indicating that Rki specifically interferes with DnaK cellular function. Finally, we show that the interaction of Rki with the host DnaK chaperone rapidly results in the stabilization of the heat-shock factor σ(32), which is normally targeted for degradation by DnaK. The mechanism by which the Rki-dependent stabilization of σ(32) facilitates RB43 bacteriophage proliferation is discussed.